Socket sclerosis, a rare complication in orthodontic tooth movement - Navneet Arora Khurana; Gaurav Khurana; Nakul Uppal (Wolters Kluwer Medknow Publications, 2010)
Socket sclerosis is usually asymptomatic and does not require any treatment. The only potential complication arises during orthodontic treatment, wherein sclerosed socket of the premolar teeth may be an obstacle in closing the space by movement of teeth through the extraction space. This article demonstrates the problems encountered during the orthodontic treatment of a 20-year-old Malaysian woman with socket sclerosis and the treatment strategy employed to overcome the same.